The multi-dimensional local limit theorem for the Markov chain in the case of the stable limit distribution law - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Алешкявичене, Многомерная локальная предельная теорема для однородной цепи Маркова в случае устойчивого предельного закона A. Aleškevičienė, Daugiamatė lokalinė ribinė teorema homogeninei Markovo grandinei stabilaus ribinio dėsnio atveju